Podjetništvo na prehodu : Global Entrepreneurship Monitor Slovenija 2004 - Rebernik, Miroslav; Tominc, Polona; Pušnik, Ksenja (2005)
Entrepreneurship in Transition: Global Entrepreneurship Monitor Slovenija 2004. The Global Entrepreneurship Monitor (GEM) research in 2004, showed a further decline in early-stage entrepreneurial activity in Slovenia. In GEM study we are primarily interested in the relative entrepreneurial orientation of the adult population and the rate of new and growing companies, as well as in differences between different countries. Under the influence of social, cultural and political context in each country a bundle of business conditions significantly affects the entrepreneurial process, exploration and exploitation of business opportunities and the capability of people to take up new ventures. Important finding of this study is that measures of economic policy on promoting entrepreneurship, must be necessarily adapted to national conditions. Promoting entrepreneurship and creating a business climate for the emergence of new and growth of existing businesses is a long term process and research findings also show that the early-stage entrepreneurship is driven by factors that are largely structural in nature and culturally conditioned.
Keywords: podjetništvo; Globalni podjetniški monitor; zgodnja podjetniška aktivnost; podjetniško okolje; podjetniške aspiracije po rasti; Entrepreneurship; Global Entrepreneurship Monitor; Early Stage Entrepreneurial Activity; Entrepreneurial Environment; Entrepreneurial Growth Aspirations